Whisker‐Implanted Biomimetic Electronic Skin for Tactile Sensing and Blind Perception - Mohammad Zarei; An Woo Jeong; Seung Goo Lee (Advanced Science)
Abstract Rodent whiskers are a distinct class of tactile sensors that work in conjunction with the biological skin to discern airstreams and obstacles with remarkable sensitivity, facilitating navigation around proximate objects. In this study, a flexible artificial skin is developed comprising sensory active units, including electronic skin (e‐skin) and an artificial whisker, inspired by the sensory capabilities of rodent skin and whiskers. As a novel strategy, unique congruent air pockets are introduced within the e‐skin to enhance the sensitivity. Mechanical stimuli applied to the artificial whisker are efficiently transmitted to the active e‐skin, which generates a sensitive tactile perception response. The developed artificial skin exhibits high sensitivity, a wide sensing range, high flexibility, superior stability, and tensile strength. The artificial whisker facilitates the sensitive detection of a broad range of applied mechanical forces. Therefore, the artificial skin can sense subtle and vigorous tactile stimuli including airstreams and field obstacles. The ability to sense, discriminate, and decipher the airstreams and obstacles imparts outstanding tactile sensing and blind perception characteristics to the artificial skin. This artificial skin is a promising platform for the development of sensitive e‐skins suitable for a broad range of applications, such as human‐machine interfaces, robotics, and wearable electronics.